M-TÜREVLİ BAZI MATEMATİKSEL MODELLEMELERİN ANALİZİ - SELÇUK, ALİ (Fırat Üniveristesi, 2024)
Bu çalışmada, Malthusian matematiksel modeli ve düşey düşüş problemleri M-türevinin Laplace dönüşümü yardımıyla yeniden çözülmüştür. Kesirli mertebeden üstel bir fonksiyon olarak elde edilen çözümler, Mittag-Leffler cinsinden elde edilen diğer kesirli mertebeden çözümlerle kıyaslanmıştır. Verilen başlangıç şartları ile Malthusian matematiksel modeli ve düşey düşüş problemleri farklı kesirli türev mertebelerinde incelenmiştir. Elde edilen sayısal değerler grafik üzerinde görsel olarak değerlendirilmiştir. Bilimsel sonuçların matematiksel analizi yapılmıştır. Anahtar Kelimeler: M-Türev, Laplace Dönüşümü, Genelleştirilmiş Kesirli Türev, Malthusian Matematiksel Modeli, Düşey Düşüş Problemi

In this study, the Malthusian mathematical model and the vertical fall problems are solved again by means of the Laplace transform of the M-derivative. The solutions obtained as a fractional order exponential function are compared with other fractional order solutions obtained in terms of Mittag-Leffler. With the given initial conditions, the Malthusian mathematical model and the vertical fall problems are analyzed at different fractional derivative orders. The numerical values obtained are evaluated visually on the graph. Mathematical analyses of the scientific results are made. Keywords: M-Derivative, Laplace Transform, Generalized Fractional Derivative, Malthusian Mathematical Model, The Vertical Motion of A Falling Body Problem
Some mathematical models analysis with M-derivative
Keywords: Matematik